Impact of Gadget Use on Speech Delay: Case Study of Toddlers in Tanjung Gusta Village - Amelia Grasela Pasaribu; Yusnadi; Muhammad Takwin Machmud (International Journal of Educational Practice and Policy, 2023)
Gadget is a term in English, which is an electronic device that has a special purpose and function to download the latest information, various technologies and the latest features so as to make human life more practical. The purpose of this study is to analyze the effect of gadget exposure on speech delay in children under five years old. This study is a qualitative descriptive analysis research. This descriptive research aims to describe a situation or phenomena as it is. This research was conducted in Tanjung Gusta Village. The subject of this research is the parents of toddlers who experience speech delay. Data collection techniques used in the study were observation and interviews. The results of observations and interviews show that children who intensely use gadgets (experimental group) have limited verbal communication skills compared to children who minimally use gadgets (control group). Children in the experimental group tended to have delayed speech, difficulty articulating words clearly and limited age-appropriate vocabulary. They also showed difficulty in understanding and following simple commands.